(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Yuliansyah. Haqiqi MT, Setiawan KA, Setiawan A, Saputra PD, Romadlon HSI, Mukhdlor A, Ramadhan R, Amirta R. 2022. Fast-growing native tree species to the secondary forest of East Kalimantan, Indonesia: Physicochemical properties of woody materials for bioelectricity feedstocks. Biodiversitas 23: 3379-3386. The conversion of woody biomass into electricity through a thermochemical process has recently attracted significant attention worldwide to promote green energy production. It provides a low-cost and straightforward operation promising for developing rural areas, especially with limited transportation access. In East Kalimantan Province, almost all remote areas are surrounded by forests with high tree species diversity, which is the potential to be utilized for sustainable feedstocks in electric power plants. This study pointed out the energy potential produced from woody biomass of selected fast-growing tree species native to East Kalimantan secondary tropical forest: Elaeocarpus ferrugineus (Jacq.) Steud., Ficus aurata (Miq.) Miq., Fordia splendidissima (Blume ex Miq.) Buijsen, Lindera lucida (Blume) Boerl., Mallotus paniculatus (Lam.) Mull. Arg. and Schima wallichii (DC). Their wood physicochemical properties were firstly investigated. Furthermore, each species’ wood quality for solid energy purposes was presented as the fuel value index (FVI). The results revealed that the change from greenwood into wood chip effectively removed the moisture content, thus improving efficiency to achieve higher energy potency. Our findings showed that the highest energy potency was obtained from the wood chip of F. splendidissima (3.61 MWh/ton), followed by S. wallichii (2.98 MWh/ton). A similar pattern was also found in FVI determination showing that the wood chip of S. Splendidissima had the greatest value (8970). Therefore, we observed that the high quality of S. splendidissima compared to other selected fast-growing species indicates its high suitability for further large-scale crop plantation to supply wood chips for biomass-based electricity generation.